2017
DOI: 10.1177/1550147717716815
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee algorithm–based efficient cluster formation and optimization scheme in mobile ad hoc networks

Abstract: In mobile ad hoc networks, topology changes very frequently due to node's mobility. Frequent change in topology increases traffic signaling that may arise energy and scalability issue. Cluster-based routing is the energy-efficient technique in mobile ad hoc networks to address the scalability issue and to minimize control messages. In this article, honey bee algorithm is used for dividing the mobile ad hoc network nodes into different clusters. The bees work to gather in groups to perform their activities. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The bee algorithm emulates honey bee foraging activities to find the optimal solution to an optimization issue. The food source or flower is considered a candidate solution, and the population of n bees searches the solution space [18]. Two important parameters of a deep learning network are the number of hidden layers and the number of neurons in each layer.…”
Section: Literature Surveymentioning
confidence: 99%
“…The bee algorithm emulates honey bee foraging activities to find the optimal solution to an optimization issue. The food source or flower is considered a candidate solution, and the population of n bees searches the solution space [18]. Two important parameters of a deep learning network are the number of hidden layers and the number of neurons in each layer.…”
Section: Literature Surveymentioning
confidence: 99%
“…The genetic algorithm selected the best cluster head based on the fitness function which was developed using the distance and energy metrics. Ahmad et al, 23 have suggested a honey bee algorithm based cluster head selection for MANET. Metrics, such as mobility direction, remaining energy, node degree, and mobility speed were considered for the cluster head selection.…”
Section: Related Workmentioning
confidence: 99%
“…is will improve farming techniques, and production cost (labor) may decrease. e MANET has widely been used for the purpose [24]. e technical nature of wireless sensor nodes makes it difficult to transmit the sensing data in a timely manner without delay.…”
Section: Hybrid Clusteringmentioning
confidence: 99%